Notification information system android-based for spreading school information - Wirawan Istiono; Jansen Sampurna (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
School is a place where students can learn a lot, but beside as a place to learning, the school also has many events and activities that must be attended by students, or even sometimes must be attended by parents. To give information or invintation to the parents, some school give information by manual letter, email, social media or online chatting, but all that method to spread information has a weakness, because sometimes information that shown or give to parents or to students, often not accepted by students or parents, and beside that, to spread message to a lot people need a lot time and need a lot cost. To solve this issue, in this study will be build Android-based information notification application with push messaging services, where if there a new information from the school, the students or parents will receive notification new information to their Android smartphone, and after that, the details of this information can be seen in the applications. To get acceptance user result, we using user acceptance test (UAT) was conducted using the TAM method, the result has positive results were 84.88% from parent or student's side and obtained 84.67% from school administration's perspective as provider information, which means this system can be accepted and as expected by the user who receiving the information and by the school as information provider.